Management of Polycystic Ovary Syndrome by Chinese Herbal Medicine Cinnamon and it’s Active Constitute: A Systematic Review and Meta-Analysis - Neha Thakur, Dishant Gupta, Archana Tiwari (International Journal of Pharmaceutical & Biological Archive, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting reproductive-aged women, characterized by hormonal imbalances, insulin resistance, and metabolic dysfunctions. Traditional Chinese herbal medicine, particularly cinnamon (Cinnamomum spp.), has gained attention for its potential therapeutic effects in managing PCOS. This systematic review and meta-analysis evaluate the efficacy of cinnamon and its active constituents in alleviating PCOS symptoms, including insulin resistance, menstrual irregularities, and hyperandrogenism. A comprehensive search of databases was conducted to identify randomized controlled trials (RCTs) and clinical studies assessing cinnamon’s effects in PCOS management. The meta-analysis revealed that cinnamon supplementation significantly improved insulin sensitivity, reduced fasting blood glucose levels, and regulated menstrual cycles compared to placebo. In addition, its active compounds, such as cinnamaldehyde and polyphenols, demonstrated anti-inflammatory and insulin-sensitizing properties. However, variations in study design, sample size, and intervention duration pose challenges in establishing definitive conclusions. Further high-quality, large-scale RCTs are necessary to validate these findings and optimize the therapeutic use of cinnamon in PCOS management. This review highlights the potential role of cinnamon as an adjunct therapy in improving metabolic and reproductive health outcomes in PCOS patients.